Trichostasis Spinulosa: A Case Report with an Unusual Presentation - Chaninan Kositkuljorn; Poonkiat Suchonwanit (Karger Publishers, 2020)
Trichostasis spinulosa (TS) is a follicular disorder characterized by the retention of multiple vellus hairs in a hyperkeratotic dilated hair follicle. TS is considered as a common disorder; however, it is often underdiagnosed due to its asymptomatic nature. Although the condition frequently affects the face or extremities, the widespread distribution of TS over the entire body has been once reported in a patient with chronic renal failure. To emphasize the infrequent presentation of TS, we herein report a 57-year-old male with an unusual location of TS.